Nutritional and antioxidative properties of black goat meat cuts - Hye-Jin Kim; Hee-Jin Kim; Aera Jang (Asian-Australasian Journal of Animal Sciences, 2019)
Objective In this study, we evaluated the nutritional value and antioxidant activity of black goat loin (BGL) and black goat rump (BGR) meat. Methods We evaluated the proximate compositions, collagen and mineral contents, and fatty acid compositions of BGL and BGR with respect to their nutritional value. The levels of bioactive compounds such as L-carnitine, creatine, creatinine, carnosine, and anserine were also measured. The ferric reducing antioxidant power (FRAP), 2,2-azinobis (3-ethyl-benzothiazoline-6-sulfonic acid) (ABTS) radical scavenging, and oxygen radical absorption capacity (ORAC) were assessed to evaluate the antioxidant activity of BGL and BGR. Results BGR showed higher collagen, Fe, Ca, P, and Na contents than did BGL (p<0.05). Notably, the Ca/P ratio was high in both BGR and BGL (1.82 and 1.54, respectively), thus satisfying the recommendation that the Ca/P ratio is between 1 and 2. BGL showed a significantly higher content of desirable fatty acids (stearic acid and total unsaturated fatty acids) than did BGR. In addition, the levels of creatine, carnosine, and anserine in BGL were higher than those in BGR (p<0.05). There was no significant difference in the antioxidant activity between BGL and BGR, as assessed by FRAP (both 15.92 μmol Trolox equivalent [TE]/g of dry matter [DM]), ABTS (12.51 and 12.90 μmol TE/g DM, respectively), and ORAC (101.25 and 99.06 μmol TE/g DM, respectively) assays. Conclusion This was a primary study conducted to evaluate the differences in nutritional value and antioxidant activity between loin and rump cuts of black goat meat. Our results provide fundamental knowledge that can help understand the properties of black goat meat.